Breast cancer stem cells: Biology and therapeutic implications. (February 2019) - Butti, Ramesh; Gunasekaran, Vinoth Prasanna; Kumar, Totakura V.S.; Banerjee, Pinaki; Kundu, Gopal C.
Highlights: Highlighting principle pathways involved in enrichment and maintenance of CSCs. The role of CSCs in metastasis, angiogenesis, drug resistance and tumor recurrence. Highlighting the drugs, miRNAs and nano-carriers for eradicating BCSCs. Highlighting the usage of anti-CSC therapy as adjuvant therapy. Abstract: Breast cancer remains to be a dreadful disease even with several advancements in radiation and chemotherapies, owing to the drug resistance and tumor relapse caused by breast cancer stem cells. Cancer stem cells are a minute population of cells of solid tumors which show self-renewal and differentiation properties as well as tumorigenic potential. Several signaling pathways including Notch, Hippo, Wnt and Hedgehog and tumor-stroma exchanges play a critical role in the self-renewal and differentiation of cancer stem cells in breast cancer. Cancer stem cells can grow anchorage-independent manner so they disseminate to different parts of the body to form secondary tumors. Cancer stem cells promote angiogenesis by dedifferentiating to endothelial cells as well as secreting proangiogenic and angiogenic factors. Moreover, multidrug resistance genes and drug efflux transporters expressed in breast cancer stem cells confer resistance to various conventional chemotherapeutic drugs. Indeed, these therapies are recognised to enhance the percent of cancer stem cell population in tumors leading to cancer relapse with increased aggressiveness. Hence, devising the therapeutic interventions to target cancer stem cells would be useful in increasing patients' survival rates. In addition, targeting the self-renewal pathways and tumor-stromal cross-talk helps in eradicating this population. Reversal of the cancer stem cell-mediated drug resistance would increase the sensitivity to various conventional drugs for the effective management of breast cancer. In this review, we have discussed the cancer stem cell origin and their involvement in angiogenesis, metastasis and therapy-resistance. We have also summarized different therapeutic approaches to eradicate the same for the successful treatment of breast cancer.